Institutional Investors, Pension Reform, and Emerging Securities Markets - Hans J. Blommestein (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper discusses the range of factors that can stimulate the further development of the domestic institutional sector through pension system reform measures. The development of the institutional sector in emerging market economies is compared with the experiences of OECD countries. The focus is on the key factors that have been (and are) driving the growth of OECD institutional investor activities and the impact of institutional investors on securities markets.
Keywords: 330